Does inflammation play a role in development of necrobiosis lipoidica? - Słowik-Kwiatkowska, Iwona; Lesiak, Aleksandra; Woźniacka, Anna; Sysa-Jędrzejowska, Anna; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction. Necrobiosis lipoidica (NL) is a granulomatous skin disease of still only partially known pathogenesis. Microangiopathy is considered as one of the most important processes in NL, and vascular endothelial growth factor (VEGF) and endothelin-1 are strongly involved in it. Recent studies have demonstrated the beneficial therapeutic effect of tumor necrosis factor α (TNF-α) inhibitors in treatment of recalcitrant cases of NL, which is due to the important role of TNF-α in development of inflammation and granulomas in the course of NL. Objective. To assess the serum levels of VEGF, endothelin-1 and TNF-α in NL patients. Material and methods . The study group consisted of 17 patients with NL (mean age 48.22 ±15.99 years), 37 patients with diabetes mellitus (mean age 52.11 ±17.41 years) and 23 healthy volunteers (mean age 44.13 ±9.33 years) as a control group. Serum concentrations of TNF-α, VEGF and endothelin-1 were assessed in all patients with the ELISA test. Results. The TNF-α concentration was statistically lower in the controls when compared to the NL patients and diabetic patients (p 0.05 for all comparisons). Endothelin-1 serum values were under the tested values in most cases; however, statistically more frequently these values were found in the controls than in the NL group (p < 0.05). Conclusions. The results of our study suggest that inflammation with enhanced synthesis of TNF-α in NL patients is the primary pathological effect, followed by local impairment of angiogenesis.